0149 Gray Matter Volume Correlates Of Sleepiness: A Voxel-based Morphometry Study In Younger And Older Adults. (27th April 2018) - Akerstedt, T; Lekander, M; Nilsonne, G; Tamm, S; d'Onofrio, P; Kecklund, G; Fischer, H; Petrovic, P; Månsson, K N
Abstract: Introduction: Sleepiness is prevalent in society, often linked to disturbed sleep, shift work, stress, or diseases. It is also associated with an increased risk of accidents. Sleepiness may be related to brain metabolism and, we hypothesize that it is associated with brain gray matter (GM) volume. The present study investigated the association between sleepiness and GM volume in thalamus and insula, with a special focus on age, since both sleepiness and GM volume change with age. Methods: In all, 84 healthy individuals participated in the experiment, of which 46 were in the age range 20–30 years and 38 ranging between 65–75 years. Data was collected in a 3 T scanner during a 5 minute anatomical scan (first in a several sessions in the scanner) in the evening after a full night of sleep. Momentary sleepiness (Karolinska Sleepiness Scale) was rated 7 times during the time in the scanner. Results: Results showed that, in older, relative to younger adults, areas within bilateral insular cortex and thalamus GM regions of interest were negatively associated (FWE-corrected) with sleepiness (Z=4.02, p=.015 left insula and Z=4.42, p=.009 for right insula; Z=3.75, p=.020 for left thalamus and Z=4.60, p=.001 for right thalamus). Larger volume was associated with low sleepiness in the older group, but not in the older group. The effect in the insula was mainly present in the mid-anterior parts of the structure.. In addition, after applying a conservative small volume correction including all ROIs simultaneously, age-interaction effects remained significant. Conclusion: It was concluded that self-rated momentary sleepiness in a monotonous situation is negatively associated with GM volume in areas within both thalamus and insula in older individuals. The results are in line with notions of thalamus as a driver of arousal and of anterior insula as a structure evaluating the state of the organism. Possibly, a larger GM volume in these structures may be protective against sleepiness in older individuals, a hypothesis that needs confirmation in further studies. Support (If Any): Bank of Sweden Tercentenary Fund.